2014
DOI: 10.1155/2014/859735
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine in Neuropsychiatric Disorders: New Advances

Abstract: D-Serine (DSR) is an endogenous amino acid involved in glia-synapse interactions that has unique neurotransmitter characteristics. DSR acts as obligatory coagonist at the glycine site associated with the N-methyl-D-aspartate subtype of glutamate receptors (NMDAR) and has a cardinal modulatory role in major NMDAR-dependent processes including NMDAR-mediated neurotransmission, neurotoxicity, synaptic plasticity, and cell migration. Since either over-or underfunction of NMDARs may be involved in the pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 190 publications
(222 reference statements)
0
16
0
Order By: Relevance
“…Benzoic acid readily crosses the intestinal barrier and BBB to inhibit D-amino acid oxidase that catabolizes D-serine, a co-agonist of N-methyl-D-aspartate receptor (NMDAR, a type of Glu receptor) . Both D-serine and NMDARs are therapeutic targets in neuropsychiatric disorders, such as depression, schizophrenia and cognitive impairment (Durrant and Heresco-Levy, 2014). Indeed, a dysfunctional Glu system is linked to the pathophysiology of depression (Pytka et al, 2016).…”
Section: Benzoic Acid and Central Glu Systemmentioning
confidence: 99%
“…Benzoic acid readily crosses the intestinal barrier and BBB to inhibit D-amino acid oxidase that catabolizes D-serine, a co-agonist of N-methyl-D-aspartate receptor (NMDAR, a type of Glu receptor) . Both D-serine and NMDARs are therapeutic targets in neuropsychiatric disorders, such as depression, schizophrenia and cognitive impairment (Durrant and Heresco-Levy, 2014). Indeed, a dysfunctional Glu system is linked to the pathophysiology of depression (Pytka et al, 2016).…”
Section: Benzoic Acid and Central Glu Systemmentioning
confidence: 99%
“…d ‐serine controls neural development, synaptic transmission, plasticity and memory (Fossat et al, ; Sultan et al, ). Compared with the placebo, acute administration of d ‐serine to healthy subjects reduced the subjective feelings of depression and anxiety (Durrant and Heresco‐Levy, ). Moreover, the glycine‐transporter‐1 inhibitor sarcosine and the d ‐amino acid oxidase (the enzyme that degrades d ‐serine) inhibitor sodium benzoate are beneficial treatments for depressed patients who have been drug‐naive for at least 3 months and have no history of treatment resistance (Huang et al, ; Lai, Lane, & Tsai, ).…”
Section: Gliotransmissionmentioning
confidence: 99%
“…Several lines of evidence have shown that changes (e.g., availability, metabolism, and/or receptor activity) in neuroactive amino acids associated with central brain functions may play a role in the pathogenesis and/or pharmacotherapy of several psychiatric disorders (e.g., schizophrenia and mood disorders) that have symptoms, such as cognitive impairment and problems with social interactions, in common with ASD (Coyle 2006; Grant et al 2006; Lam et al 2006; Labrie et al 2008; Ongür et al 2008; Yüksel and Öngür 2010; Durrant and Heresco-Levy 2014). Several preclinical and clinical studies have implicated neuroactive amino acids in the etiology of ASD, fragile X syndrome, and tuberous sclerosis complex (TSC), but most of these studies have focused on glutamate, GABA, and/or glutamine (El-Ansary and Al-Ayadhi 2014; Rojas 2014; Santini et al 2014; Rozas et al 2015; Cochran et al 2015; Lozano et al 2015; Robertson et al 2016).…”
Section: Neuroactive Amino Acidsmentioning
confidence: 99%